A comparative study of prostate PTV margins for patients using hydrogel spacer or rectal balloon in proton therapy. (January 2021) - Su, Zhong; Henderson, Randal; Nichols, Romaine; Bryant, Curtis; Hoppe, Bradford; Mendenhall, William; Mendenhall, Nancy
Highlights: Analyzed the patient setup data and prostate intrafraction motion data for patient using rectal balloon or hydrogel spacer. Obtained systematic errors and random errors of patient setup residual and prostate intrafraction motion. Calculated required PTV margins and their uncertainties for both patient cohorts. Abstract: Purpose: To compare the planning target volume (PTV) margins needed for prostate patients who have used hydrogel spacer or rectal balloon during proton treatments. Method: Total of 190 prostate patients treated with proton therapy during 2017 were selected for this study. Of these patients, 96 had hydrogel spacer injection and 94 patients had only rectal balloons insertion. All patients had implanted gold markers inside the prostate for daily target alignment. Post-treatment radigraphs were obtained to evaluate prostate intrafraction motion. The systematic and random components of patient setup residual error and prostate intrafraction motion error were obtained. PTV margins were calculated using the van Herk formula for both patient groups. Results: For setup residual error, the mean values in the superior-inferior (SI) direction and the variances in the left–right (LR) direction were statistically different between the two groups. For intrafraction motion, there were significant differences of the mean values in the SI direction and of the variances in both LR and anterior-posterior (AP) directions. The population PTV margins for hydrogel spacer group were 2.6 mm, 3.3 mm, and 1.6 mm in LR, SI, AP directions, respectively. For the rectal balloon group, the PTV margins were 2.1 mm, 3.1 mm, and 2.0 mm in LR, SI, AP directions, respectively. Conclusion: Statistically significant differences were observed in the patient setup and prostate intrafraction motion errors of the two patient groups. However, under the current protocol of bladder preparation and daily marker-based x-ray image-guidance, population PTV margins were comparable between the two patient groups.